2021
DOI: 10.1007/s11356-021-14980-6
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between measles immunization coverage and overall morbidity and mortality for COVID-19: an epidemiological study

Abstract: We conducted the current analysis to determine the potential role of measles vaccination in the context of the spread of COVID-19. Data were extracted from the World Health Organization’s (WHO) Global Health Observatory data repository about the measles immunization coverage estimates and correlated to overall morbidity and mortality for COVID-19 among different countries. Data were statistically analyzed to calculate the Spearman rank correlation coefficient (rho). There was a significant positive correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The B cell cross-reactivity with SARS-CoV-2 antigens was also reported in MR-vaccinated children [24], and statistical correlation between the SARS-CoV-2-specific B cell activation and serum level of anti-measles antibody was suggested [22]. On the other hand, there are some negative data on the protective role of such live attenuated vaccines against COVID-19 outcomes [25] [26]. Our results warrant further investigation on unmeasured confounders or interactions (effect modifications) around the possible protective factor (MR vaccination).…”
Section: Discussionmentioning
confidence: 99%
“…The B cell cross-reactivity with SARS-CoV-2 antigens was also reported in MR-vaccinated children [24], and statistical correlation between the SARS-CoV-2-specific B cell activation and serum level of anti-measles antibody was suggested [22]. On the other hand, there are some negative data on the protective role of such live attenuated vaccines against COVID-19 outcomes [25] [26]. Our results warrant further investigation on unmeasured confounders or interactions (effect modifications) around the possible protective factor (MR vaccination).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation was detected between the activation of memory T-cells during COVID-19 infection in individuals who had previously received these two vaccines [22]. However, in an epidemiological study that was conducted using the World Health Organization (WHO) Global Health Observatory data, MMR vaccination rates of countries and the number of COVID-19 and death rates were compared, and it was found that vaccination did not have a protective effect on the disease [23]. In the study of Gold et al, no correlation was detected between Measles antibody titers and COVID-19 severity [24].…”
Section: Discussionmentioning
confidence: 99%